2016
DOI: 10.1007/s13157-016-0835-7
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Measures of Coastal Wetland Condition: Implementation at a Laurentian Great Lakes Basin-Wide Scale

Abstract: Since European settlement, over 50 % of coastal wetlands have been lost in the Laurentian Great Lakes basin, causing growing concern and increased monitoring by government agencies. For over a decade, monitoring efforts have focused on the development of regional and organism-specific measures. To facilitate collaboration and information sharing between public, private, and government agencies throughout the Great Lakes basin, we developed standardized methods and indicators used for assessing wetland conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 55 publications
3
92
0
Order By: Relevance
“…Although it is worth noting that the influence of morning versus evening on detection was much less among broadcast species and American Bittern. Detection of about one-third of these species was significantly higher during morning (Common Gallinule, Pied-billed Grebe), significantly higher during evening (American Bittern, Sora, Virginia Rail), or showed no significant difference (American Coot, Least Bittern), which supports the use of morning as well as evening surveys in monitoring programs targeting elusive marsh bird species (e.g., Tozer 2013, 2016, Uzarski et al 2017. We also found that detection in many of the species was significantly higher for the MMP compared to the CWMP, the reasons for which are unclear, but perhaps related to differences in species abundances and sampling locations.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…Although it is worth noting that the influence of morning versus evening on detection was much less among broadcast species and American Bittern. Detection of about one-third of these species was significantly higher during morning (Common Gallinule, Pied-billed Grebe), significantly higher during evening (American Bittern, Sora, Virginia Rail), or showed no significant difference (American Coot, Least Bittern), which supports the use of morning as well as evening surveys in monitoring programs targeting elusive marsh bird species (e.g., Tozer 2013, 2016, Uzarski et al 2017. We also found that detection in many of the species was significantly higher for the MMP compared to the CWMP, the reasons for which are unclear, but perhaps related to differences in species abundances and sampling locations.…”
Section: Discussionmentioning
confidence: 65%
“…Lawrence region (Burton et al 2008, Tozer 2013, 2016, Uzarski et al 2017 Meixler 2008), it might require ~US$112,000-331,000 (estimated in 2017 currency) to survey these additional points using 15-min counts. By using 10-min instead of 15-min point counts, one essentially gains, at almost no additional cost, a ~12-38% increase in sample size and associated statistical power in exchange for small reductions in detection probabilities for some species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations